UPS design using lithium-ion batteries, automatic smart charging, and monitoring with blynk application - Evi Suhaevi; Ayu Febrina Rizal; Azmi Rahadi (Jurnal Scientia, 2024)
This study aims to determine the results of UPS design using Lithium ION batteries, automatic smart charging, and monitoring with the Blynk application. This study uses an experimental research design to test and implement Uninterruptible Power Supply (UPS) that uses Lithium-Ion batteries and Automatic Smart Charging with monitoring through the Blynk application. An Uninterruptible Power Supply (UPS) is an electrical backup device in case of a sudden power outage. A modified Valve Regulated Lead Acid (VRLA) battery replaces it with an 18650 Lithium-ion battery, which is parallelized in series to produce the same 12V voltage. DC because this Lithium battery has a longer life than VRLA batteries. In this final project, the author uses the Blynk application to monitor batteries and automatic smart charging, making it easier and more practical. The results of this study state that the tool can operate optimally without hurting the electronic devices tested.